Princely Rings with Heraldic Plots (the End of XII — the First Half of the XIII Century) - Котик, Ю. (Київський національний університет імені Тараса Шевченка, 2025)
Relevance of the research. Sphragistic monuments are an important source of Ukrainian studies, especially when it comes to the study of pre-Mongol Rus. The iconographic subjects presented on them allow, among other things, to find out complex issues related to the functioning of the princely power and its presentation. In the signs and symbols, which are engraved on seals and rings, a complex system of ideas inherent in society of that time in exercising powers of authority, origin and dynastic ties of the princely lineage are reproduced. The purpose of the article is to publish new materials that allow you to draw conclusions about the time of appearance and spread heraldic lion and jackdaw in the territory of Galician land .Conclusions. Sphragistic plots provide an opportunity to supplement the information in written sources about the peculiarities of the princely power functioning of pre-Mongol Rus. The article introduces previously unpublished monuments – signet rings with heraldic figures of the princes of the Galician land, analyzes the use of heraldic plots on newly discovered Galician-type rings in the context of the development of the heraldic tradition in the territory of the Galician land in the 12th–13th centuries. The images of the jackdaw presented on the rings are one of the oldest evidence of the spread of the heraldic figure in the territory of the Galician land, which already from the 13th century onwards was in use as its heraldic sign. In view of this, there is every reason to attribute the time of the appearance of heraldic of the Galician land to the end of the 12th century, which makes it possible to identify it as one of the oldest land coats of arms in the territory of Ukraine-Rus.Keywords: iconography, coat of arms, heraldry, signet ring, jackdaw, lion, Galician land.

Актуальність. Важливим джерелом українознавства є сфрагістичні пам’ятки, особливо якщо йдеться про вивчення домонгольської Русі. Іконографічні сюжети, що представлені на них, дають можливість, крім іншого, з’ясувати складні питання, пов’язані з функціонуванням княжої влади та її презентацією. У знаках і символах, що їх викарбувано на печатках і перснях, відтворено складний комплекс уявлень тогочасного суспільства щодо здійснення владних повноважень, походження та династичних зв’язків княжого роду.  Метою статті є публікація нових матеріалів, що дають можливість зробити висновки про час появи та  поширення на теренах Галицької землі гербових фігур лева та галки. Висновки. Сфрагістичні сюжети дають можливість доповнити відомості письмових джерел про особливості функціонування княжої влади домонгольської Русі. У статті введено у науковий обіг раніше не опубліковані пам’ятки – персні з гербовими фігурами князів Галицької землі, проаналізовано уживання гербових сюжетів на нововиявлених перснях галицького типу в контексті розвитку геральдичної традиції на теренах Галицької землі ХІІ–ХІІІ ст. Представлені на перснях зображення галки є одним із найдавніших свідчень поширення на теренах Галицької землі гербової фігури, що вже від ХІІІ ст. і надалі уживалася як її геральдичний знак. З огляду на це є всі підстави віднести час появи герба Галицької землі на кінець ХІІ ст., що дає змогу ідентифікувати його як один із найдавніших земельних гербів на теренах України-Русі. Ключові слова: іконографія, герб, геральдика, перстень, галка, лев, Галицька земля.
Княжі персні з геральдичними сюжетами кінця ХІІ— першої половини ХІІІ століття